Chemical, Nutritional, Physical and Sensory Characterization of Tempe Made from Various Underutilized Legumes - Wikandari, Rachma; Nurul Utami, Tiara Anjarsari; Hasniah, Nurul; Sardjono (Pakistan Journal of Nutrition, 2020)
Background and Objective: The exploration of a new food resource is important with the inevitably fast-growing global population. This study aimed to characterize the chemical, nutritional, physical and sensory properties of tempe made from various underutilized legumes. Materials and Methods: The chemical and nutritional characterization included proximate analysis and antinutrient compound determination, amino acid profiles and micronutrient analysis. Moreover, the sensory evaluation included that of appearance, texture, aroma, taste and overall acceptance and the physical characterization included texture and color analyses. The underutilized legumes used in this study were mung bean, cowpea, black soybean, kidney bean, groundnut and velvet bean. Tempe made from yellow soybeans, which is commonly consumed, was used as a control. Results: In terms of nutrition and chemical composition, black soybean was superior to the others and exhibited better properties than those of the control. On the other hand, the overall panelist acceptability of tempe made from underutilized legumes was lower than that of the control. Conclusion: This study found that underutilized legumes were potential raw material for making tempe. However, education, promotion and habituation will be needed to increase their acceptability by consumers.